CFD modelling of the hydrodynamics of scrap tyre in a fluidized bed reactor (2015)
Fluidization is one of the most promising technologies to transform waste materials (biomass, plastics and end-of-life tyres) into useful products via thermochemlcal processes. This technology has been investigated computationally using CFD as a tool for the design of the reactor. Most literature regarding CFD techniques focus on the fluidization of biomass particles. However, there are very few computational studies regarding the fluidization of scrap tyre particles. The composition and density of these particles affects significantly the dynamics inside a fluidized bed reactor. In this work, the dynamics of tyre particles in a fluidized bed were investigated both numerically and experimentally. The applied methodology consisted in two different approaches: a 2D approach, where bubble characteristics where analyzed and a 3D approach, where pressure drop was compared. An Eulerian-Eulerian approach with two different drag models was used for the computational model. The results show that the Eulerian-Eulerian approximation does not predict well the behavior of tyre particles in a fluidized bed reactor. Bubble diameter and rise velocity are highly overpredicted while the bed expansion is underpredicted. On the other hand the pressure drop from the computational model seems to fit well the experimental findings above the minimum fluidization velocity. Nonetheless the pressure drop below the minimum fluidization velocity is not well predicted. The discrepancy may be attributed to the fact that tyre particles are classified as Geldart A particles and hence, the dynamics are more complex and cannot be well predicted using a standard Eulerian-Eulerian approach.